(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
Anatomical reinterpretation of a horn-core from the Ponte Milvio site, previously ascribed to Bubalus murrensis, suggests that it belongs to the species Hemibos galerianus, originally described from the type locality of the Galerian Land Mammal Age (LMA). This is the second record in the Italian Pleistocene of this rare Bovini species, derived from the genus Hemibos of Indian origin.